Percutaneous Endoscopic Gastrostomy Feeding in Children with Cerebral Palsy - Civan, Hasret Ayyildiz; Bektas, Gonca; Dogan, Ali Evrim; Ozdener, Fatih (Neuropediatrics, 2021)
Aim The prevalence of congenital cerebral palsy (CP) worldwide ranges from 0.15 to 0.4%. CP causes several gastrointestinal complications that inhibit normal eating behavior. This single-center observational study aimed to determine the tolerability and benefits of percutaneous endoscopic gastrostomy (PEG) in pediatric CP patients with malnutrition.Materials and Methods The study included 41 pediatric CP patients with malnutrition. All patient data were retrospectively obtained from Bakırköy Dr. Sadi Konuk Research and Training Hospital, Department of Pediatric Gastroenterology, Hepatology, and Nutrition, Istanbul, Turkey. In addition to baseline measurements of weight, height, triceps skinfold thickness, 1,25-hydroxyvitamin D3, folate, iron, zinc, vitamin B12, hemoglobin, and mean corpuscular volume, data analyzed included follow-up measurements recorded at 3 and 6 months of PEG (standard polymeric enteral supplementation as 1.0 kcal mL–1).Results There was significant improvement in both height, weight, and triceps skinfold thickness in all patients at 3 and 6 months of PEG (p < 0.05). In terms of blood parameters, there was not significant improvement, except that the number of patients with a low hemoglobin count significantly decreased at 3 and 6 months of (p = 0.022). Moreover, the number of patients with vomiting after PEG also significantly decreased at 3 and 6 months of (p = 0.004).Conclusion PEG significantly improves malnutrition in pediatric CP patients and does not cause any major complications. Based on these findings, we think PEG is a beneficial and cost-effective intervention with a high rate of tolerability in pediatric CP patients with malnutrition.
Keywords: cerebral palsy; malnutrition; pediatric; neurological disorders